2015
DOI: 10.1109/jbhi.2014.2311044
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-Based Analysis for Personalized Stress Evaluation Using Physiological Signals

Abstract: Technology development in wearable sensors and biosignal processing has made it possible to detect human stress from the physiological features. However, the intersubject difference in stress responses presents a major challenge for reliable and accurate stress estimation. This research proposes a novel cluster-based analysis method to measure perceived stress using physiological signals, which accounts for the intersubject differences. The physiological data are collected when human subjects undergo a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(78 citation statements)
references
References 19 publications
0
74
0
4
Order By: Relevance
“…This approach allowed to increase accuracy by 12% compared with the general model. Xu et al [36] studied stress detection with neural networks using physiological data, collected in a lab; clustering of the test subjects was also based on their unlabelled data. Assigning of 44 subjects to two clusters allowed to increase accuracy (i.e.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach allowed to increase accuracy by 12% compared with the general model. Xu et al [36] studied stress detection with neural networks using physiological data, collected in a lab; clustering of the test subjects was also based on their unlabelled data. Assigning of 44 subjects to two clusters allowed to increase accuracy (i.e.…”
Section: Related Workmentioning
confidence: 99%
“…each target individual had to provide about 60 self-reports [10,21]. In addition, it was observed that success of reusing data of other individuals strongly depends on the degree of similarity between these individuals and the target person [21,36].…”
Section: Introductionmentioning
confidence: 99%
“…Many research studies use psychophysiological signals collected during stress induced by solving mental tasks in the laboratory environment [42,[44][45][46][47][48]. These tasks usually involve solving logical puzzles, mathematical equations, or dealing with time-sensitive challenges.…”
Section: Comparison Of Resultsmentioning
confidence: 99%
“…Both of them are able sensors and bio signal processing technologies to be developed for detecting the human stress. There are few types of bio signal processing technologies use for human stress detection such as Electrocardiography (ECG), Electromyography (EMG), Electroencephalography (EEG), Blood Pressure (BP), Blood Volume Pulses (BVP) and Galvanic Skin Resistance (GSR) [6]. The reaction of an athletes towards recovery process can be identified by using EEG.…”
Section: Introductionmentioning
confidence: 99%